Five new species in the genus Leschenaultia Robineau-Desvoidy, 1830 (Diptera: Tachinidae) from Mato Grosso, Mato Grosso do Sul and Rondônia, Brazil - Toma, Ronaldo (Zootaxa, 2019)
Five new species of Leschenaultia Robineau-Desvoidy, 1830 are described and illustrated based on SISBIOTA-Diptera project material collected in three Brazilian states: Leschenaultia andarae sp. n. and Leschenaultia belkysae sp. n. from Mato Grosso; Leschenaultia frangeri sp. n. and Leschenaultia marjorieae sp. n. from Mato Grosso do Sul; and Leschenaultia liriai sp. n., the first record of this genus from Rondônia. Leschenaultia bicolor (Macquart, 1846) is recorded for the first time from Mato Grosso do Sul. A key to all Brazilian species of Leschenaultia is provided.